2021
DOI: 10.1530/joe-21-0134
|View full text |Cite
|
Sign up to set email alerts
|

Necrostatin-1 reduces cardiac and mitochondrial dysfunction in prediabetic rats

Abstract: High fat diet (HFD) consumption induces prediabetes and left ventricular dysfunction through many pathways including the cell death pathway, necroptosis. Although benefits of necroptosis inhibitor (necrostatin-1 or Nec-1) in the brain of prediabetic rats have been shown, the effects of Nec-1 on cardiac autonomic function, blood pressure, and cardiac function, and the mechanisms involved have not been investigated. Male Wistar rats were fed with either a normal diet (n=8) or HFD (n=24) for 12 weeks to induce … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…These in vitro studies have engaged the necroptosis signaling in high glucose-induced cardiomyocyte death. In animal models of diabetes including STZ injection-induced type-1 diabetic mice [ 27 ], high fat diet-induced pre-diabetic rats [ 25 ], high fat diet plus STZ-induced type-2 diabetic rats [ 43 ] and db/db type-2 diabetic mice [ 27 ], the protein levels of total and/or phosphorylated RIPK1/RIPK3/MLKL were elevated in the heart, suggesting a potential role of necroptosis in cardiac complications of diabetes. Indeed, this was supported by a most recent study which showed that deletion of RIPK3 alleviated myocardial injury and dysfunction in STZ-injected mice [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These in vitro studies have engaged the necroptosis signaling in high glucose-induced cardiomyocyte death. In animal models of diabetes including STZ injection-induced type-1 diabetic mice [ 27 ], high fat diet-induced pre-diabetic rats [ 25 ], high fat diet plus STZ-induced type-2 diabetic rats [ 43 ] and db/db type-2 diabetic mice [ 27 ], the protein levels of total and/or phosphorylated RIPK1/RIPK3/MLKL were elevated in the heart, suggesting a potential role of necroptosis in cardiac complications of diabetes. Indeed, this was supported by a most recent study which showed that deletion of RIPK3 alleviated myocardial injury and dysfunction in STZ-injected mice [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although activation of RIPK3 and MLKL necroptosis signaling has recently been reported in diabetic hearts [22][23][24][25][26][27], direct evidence of cardiomyocyte necroptosis is lacking in the heart. To characterize cardiomyocyte necroptosis in the heart in situ, we first determined necrosis in the hearts of STZ-induced type-1 diabetic mice.…”
Section: Cardiomyocyte Necroptosis Is Induced In a Mouse Model Of Stz...mentioning
confidence: 99%
See 1 more Smart Citation
“…There were studies conducted on the potential therapeutic effect of Nec-1 in many diseases affecting all organ systems. Briefly, the neuroprotective effect of necrostatin in ischemic injuries (Liu et al, 2019a;Mitroshina et al, 2022), hydrocephalus (Liu et al, 2021a), mitochondrial dysfunction (Apaijai et al, 2021), intracranial hypertension (Qian et al, 2022) was revealed. Necrostatin reduces postoperative cognitive dysfunction (Yin et al, 2022), neonatal neurotoxicity (Xu et al, 2021b), and cardiotoxicity (Erdogmus Ozgen et al, 2022).…”
Section: Ripk1 Inhibitorsmentioning
confidence: 99%
“…Similarly to Mfn2 over-expression, treatment of HFD-induced prediabetic mice with necrostatin-1, an inhibitor of cell death and inflammation receptor RIPK1, with known cardioprotective properties [ 41 ], effectively enhanced Mfn2 protein levels, with no alterations in Mfn1 and Opa1 protein levels, thus increasing mitochondrial fusion and alleviating mitochondrial dysfunction. In addition, necrostatin-1 effectively reduced cardiac dysfunction, cardiac autonomic imbalance, and blood pressure in prediabetic rats [ 42 ].…”
Section: Mitochondrial Dynamics In Dcmmentioning
confidence: 99%